HOW PUBLICATION ON THE RESEARCH SKILLS DEVELOPMENT FRAMEWORK AS USEFUL EVIDENCE FOR ACADEMICS WORKING DURING PANDEMIC DISRUPTION - Normuslim Normuslim; Ahmad Ahmad; Nur Arif Nugraha; Dayan Abdurrahman (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
This study reviewed some publications on the benefits of implementing the Research Skills Development (RSD)Framework as evidence for academicians and students at the higher education level in carrying out assignments involving research-based learning activities and other scientific work. Higher education learning experts believe that learning and working at a distance mode, especially in the pandemic disruption, is greatly assisted by developing research skills application. This paper has reviewed many scientific publications of the RSD framework and other research-based learning literature to gain a better perspective and understanding to prove this assumption. With the existing research evidence from seven publication materials, we could say that the evidence from the Research Skill Development framework's publications and advantages are constructive for academic and students in universities where the involvement of rich research skills is very high and specific as they now are working in the remote system during the crisis of infected pandemic. Therefore, we highly recommend academicians, students in the higher education environment. In addition, more researchers outside academia to restudy the conceptual framework and its assessment rubric matrix in their scientific work for publication or internal university marking purposes in future investigation.